Strategy for the restaurant business in Russia in terms of sanctions and import substitution - Andreeva , Irina; Litvinenko , Tatiana; Chalkin , Andrey (Applied Studies in Agribusiness and Commerce, 2017)
This article describes the situation established in August 2014 in Russia. The article considers an example of a famous restaurant «Metropol» (Moscow), taking into account the prevailing situation in Russia. The study of customer attendance, assortment and price policy towards the main products forming the restaurant’s menu was conducted. As a result, recommendations were given, in order to preserve the client base and revise the assortment of dishes.JEL CODE: M21